MANAGEMENT FISIOTERAPI PADA FRAKTUR TIBIA DI RS UNIVERSITAS SEBELAS MARET SURAKARTA: CASE REPORT - Rochmah, Yunita Nur; Isnaini Herawati (Bajang Institute, 2024)
Introduction: A fracture is defined as a break in the continuity of the cortex of the bone. Purpose: of this study is to determine the implementation of physiotherapy in overcoming pain reduction, increase range of motion and improve functional ability in cases ⅓ proximal tibia fibula sinistra. Methods: resistance exercise, hold relax, strengthening exercise, walking exercise full weight bearing exercise of the patient is given for 4 weeks. Results: evaluation was carried out using ROM (Range of Motion,), Manual Muscle Testing, and Numeric Rating Scale, Foot And Ankle Disability (FADI). Conclusion: there is an increase in ROM (Range of Motion,), Manual Muscle Testing, Numeric Rating Scale, Foot Ankle Disabilty Index for 4 weeks.